Jerusalem between religion and international politics - نەجم, خەسرەو عەبدولڕەحیم (Sulaimani Journal for Humanities, 2019)
This is a brief summery of a post-doctorate research, relying on the academic and scientific resources of the Vatican conducted in 2017. The research is an attempt to review the historical roots of Jerusalem. Mostly, Jerusalem is known through the problem of Arabs and Jews, without acknowledging the sanctity of this city for Christians whom their number more than two billion and two hundred million people in the world. It is true that Jerusalem is a mosaic of religion and nationalities, which it has Muslim, Christian and Jewish holy shrines. This creates a race for international control over the city and made it an international political problem. The struggle between the catholic, orthodox, protestant and Armenian have made America, Russia, Europe and Vatican to interfere. These sides made religion a tool for strengthening their standing in those regions. Palestine is a sacred place for the Christians; it has a deep relation with the history of their religion: Jesus was born in Bethlehem, his crucifixion and raising his soul to heaven happened there. Because of these specifications the popes of Rome and Vatican always had a moderate strategy to keep the coexistence of the religions and to allow the religious individuals to visit their sacred places without any problem. In those circumstances from the nineteenth century, the arab- jew relationship became complicated, specifically after the appearance of the following two factors: first, the establishment of Zionist movement which made the return to Palestine its target. Second, since then, Britain made its standing stronger there and by the Belfour Declaration 1917 announced its support to the Zionist project. A Jewish exodus started and changed the demography of the area. One of the forces that stayed against the growth of Jewish power, side by side with the Christian and Muslim Arabs, were the popes of the roman church and the Vatican. However the Jew, with the help of Zionist movement and the British in 1948 established the State of Israel and empowered itself on Jerusalem. Therefore, the project of the globalisation of Jerusalem which was in the benefit of each side stayed incomplete.